A Model for Developing Grammatical Educational Materials Using a Mind Mapping-Based Graphical Approach at the Kadiri "Kalam" Education Council. - NURYANTO, NURYANTO; Umar Faruq, Umar Faruq; Yuyun, Yuyun Zunairoh; Anang, Mohamad Anang Firdaus (Asalibuna, 2024)
Abstract:    This study aims to (1) examine the implementation of Nahwu material using the Rosam Albayani method with mind mapping to improve reading skills at Majelis Taklim Alkalaam, (2) analyze its impact on learners’ understanding of Arabic grammar, and (3) identify the characteristics of the developed textbook suitable for non-formal learning contexts. The research applied the Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The process began with a needs analysis of learners from diverse educational backgrounds. Learning materials were designed based on visual mind mapping, validated by experts, and implemented in practice. Instrument testing showed validity, with all items exceeding the r-table value (0.396) at a significance level < 0.05. Reliability analysis produced Cronbach’s Alpha scores of 0.722 (pre-test) and 0.874 (post-test), confirming consistency. Normality tests using Shapiro-Wilk indicated data distribution was normal (pre-test 0.445; post-test 0.221). A paired t-test revealed a significant improvement, with average scores rising from 26.00 to 54.40 (p = 0.000 < 0.05). The findings demonstrate that the Rosam Albayani Nahwu textbook is effective, adaptive, and engaging for learners in non-formal settings, providing an innovative solution for strengthening Arabic grammar comprehension.   ملخص:   يهدف هذا البحث إلى دراسة تطبيق مادة النحو بطريقة الرسم البياني القائم على الخريطة الذهنية في مجلس التعليم "الكلام"، وبيان أثرها في تنمية مهارة القراءة وفهم البنية النحوية، إضافةً إلى تحديد خصائص الكتاب التعليمي المناسب للمتعلمين في البيئات غير الرسمية. اعتمد الباحث منهج البحث والتطوير (R&D) وفق نموذج ADDIE (التحليل، التصميم، التطوير، التطبيق، التقييم). بدأ العمل بتحليل حاجات المشاركين ذوي الخلفيات المتنوعة، ثم طُوِّرت المادة التعليمية وفق التصور البصري بخريطة المفاهيم، وقُيِّمت من قِبل الخبراء قبل تطبيقها ميدانيًا. أظهرت نتائج الصدق والثبات أن أدوات الاختبار صالحة وموثوقة (كرونباخ ألفا 0.722 و0.874). كما أثبت اختبار شابيرو-ويلك أن البيانات تتبع التوزيع الطبيعي، وأظهر اختبار "ت" للعينات المرتبطة فروقًا دالة بين الاختبار القبلي (26.00) والبعدي (54.40) بقيمة دلالة 0.000 < 0.05. وعليه، خلص البحث إلى أن طريقة الرسم البياني بالخريطة الذهنية فعّالة ومناسبة لتعليم النحو في السياقات غير الرسمية